Crisi ecologica e processi di “identizzazione”. L’esempio delle estrazioni petrolifere in Basilicata - Enzo Vinicio Alliegro (EtnoAntropologia)
In Agri Valley, Basilicata (Italy), oil companies have opened the largest production of continental Europe. The oil industry is located close to a National Park, in a territory rich of water and landscape resources where there is a very important agricultural tradition. The essay, through field research and the use of extensive archival documentation, seeks to analyze the conflicts and the cultural changes products by the presence of oil companies that have produced a capillary redefinition of cultural identity, here called "identizzazione".